Status Reproduksi Belut Sawah (Monopterus albus) yang tertangkap di Desa Kalitinggar, Kabupaten Purbalingga - Sa'adatul Amalia; Priyo Susatyo; Sugiharto Sugiharto (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Ricefield eel is one type of fish whose habitat is in paddy fields and the eel's body does not have scales. Ricefield eel has a high protein, so it is widely consumed and sold in local and international markets. Eel reproduction is a protogynous hermaphrodite thathas a replacement cycle from female sex to the male sex. This research was conducted in the laboratory of the Faculty of Biology, Jenderal Soedirman University, by taking samples of Ricefield Eel in Kalitinggar Village, Padamara District, Purbalingga Regency. The purpose of this study was to know the relationship between GSI with a certain eel body length, as well as the gonad histology picture of rice eels in each fishing month. The results of the study as many as 54 eel catches. Ricefield eel was caught in May, June, and August 2019. Eel body length ranges from 16-35 cm with a GSI value of 0.32 – 10.36 %. There is a correlation between eels' body length toward GSI with the value p < 0.01, which was tested using Pearson correlation in the SPSS application. Based on observations using a microscope, many of the eels produced females with a body length ranges of 19-32 cm.